The Chemical Content Of Different Energy Crops (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents the data of gaseous and alkali elements in above-ground biomass of energy crops. The investigations objects were Phalaris arundinacea L., Populus nigra, Artemisia vulgaris, Sylphium perfoliatum, Sida hermaphrodita, Dactylis glomerata, Salix viminalis, Medicago sativia L. The aim of the research: to evaluate the amount of chemical elements in energy crops. Evaluating the energy crops it can be seen, that the most alkaline metals are contained in Sida hermaphrodita, and the least in Sylphium perfoliatum L.